Causes and consequences of juvenile delinquency in India - Haveripet, Prakash (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> As per the statistics available, there are 10.2 juvenile offenders per 1 lack population in the world. In India the percentage of recorded juvenile crimes are about 0.9 to 1 % of total crimes. Juvenile delinquency is one of the burning issues all over the world. The paper has been designed to explore the causes, consequences and diversity of criminal activities by juvenile delinquents. Sample has been selected purposively and social survey method is used to collect data. It is revealed from the study that, no particular reason is responsible for juveniles’ delinquency- a variety of reasons are responsible for this. Lack of proper family control, conflict in family, situation of residential area, impact of movies etc. are equally responsible for the juvenile delinquency. A number of juveniles are incapable to maintain their basic needs and to get proper recreation from their family. Consequently, they are involving in many anti-social activities to fulfill their basic needs and recreation through earning money.